Multiplication of criminal liability related to failure to pay remuneration on time from the perspective of the legal basis of employment - Kowalski, Sebastian (The use of atypical forms of employment in violation of labour and social security laws - diagnosis and prospects for the future, 2023)
The article is devoted to the criminal liability related to the non-payment of remuneration for work on time, as well as the non-payment of public tributes closely related to remuneration. The author analyses the scope of this protection depending on the basis of employment of the person whom the employing party has failed to pay the wages due.